Grape seed extract effects on serum amylase levels and immunohistochemical alterations in Streptozotocin-induced diabetic rats - Irak, Kıvanç; Yıldırım, Serkan; Mert, Handan; Mert, Nihat (Cellular and Molecular Biology, 2018)
In this study, serum amylase activity and structural changes of the pancreatic tissue in rats under the effects of grape seed extract were investigated. Thirty-two female Wistar albino rats were divided into 4 groups. First one was the control group. The second group was the streptozotocin (STZ)-induced diabetes mellitus (DM) group (45 mg/kg), while the third group was the grape seed extract (GSE) group, where the GSE was administrated intragastrically for 20 days (at 0.6 ml/rat). Lastly, the fourth group was the diabetes mellitus+GSE (DM+GSE) group. Blood samples were taken and analyzed for amylase activity. Caspase 3 expressions were inspected with immunohistochemistry. Amylase levels in the diabetic group were found to be the lowest (794.00±44.85 U/L, p<0.001), while the GSE group had the highest value (1623.63±80.04 U/L, p<0.001) Number of apoptotic cells was increased in Langerhans islets of the diabetic group. In the control and GSE groups, the apoptotic cells were found to be almost entirely absent. Increased number of apoptotic cells was found in the DM group, while decreased number of apoptotic cells was found in the DM+GSE group. Furthermore, atrophy in Langerhans islets, hyperemia in capillary veins, hydropic degeneration and necrosis in islet cells were determined in the diabetic group. Only mild hydropic degeneration in islet cells of Langerhans was observed in the DM+GSE group. Histopathologically beneficial changes in the pancreases were detected when grape seed extract was given to diabetic rats. As a conclusion, GSE was determined to have positive effects on the function and structure of the pancreas, improving enzyme activities and the structure of the Langerhans islets.